ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN BERWIRAUSAHA PADA ALUMNI SMK DI KABUPATEN PURWOREJO - Fadhiliya, Lukman; Sulistyadi, Kohar; Murtini, Wiedy (Jurnal Pendidikan Insan Mandiri, 2014)
The purpose of this study is to obtain: 1) the influence of several characteristics that influence entrepreneurial success entrepreneurship, 2) factors characteristic of the entrepreneurial spirit among some of the most dominant influence entrepreneurial success, and 3) the influence of the characteristics of the entrepreneurial spirit of the most dominant influence on the success of entrepreneurship in vocational graduates Purworejo.This research is quantitative research methods that ex-post facto research is correlational (correlation studies). The study population was all vocational school graduates in the district that are categorized Purworedjo has become a successful entrepreneur. The sample was 60 alumni population taken by purposive sampling technique. Data collection techniques used were questionnaires (questionnaire). Techniques of data analysis performed by factor analysis and multiple linear regression.The results of this study are as follows: 1) the characteristics of the entrepreneurial spirit shown to have a high impact on the success of entrepreneurship, 2) the dominant factor affecting the success of entrepreneurship in having a clear vision and purpose, confidence (self-confidence), and has the soul of a leader, 3) vision and goals positive and significant impact on the success of entrepreneurship, self-confidence and a significant negative effect on the success of entrepreneurship, soul leader, and a significant positive effect on the success of entrepreneurship.Keywords:Characteristics of the Spirit of Entrepreneurship, Entrepreneurship             Success, Factor Analysis, Principal Component Analysis.